Effectiveness of long-acting antipsychotics in clinical practice: 2. Effects of antipsychotic polypharmacy on risperidone long-acting injection and zuclopenthixol decanoate. (April 2016) - Cordiner, Matthew; Shajahan, Polash; McAvoy, Sarah; Bashir, Muhammad; Taylor, Mark
Objectives: Antipsychotic polypharmacy (APP) is common clinical practice. Theoretically, APP runs the risk of additional side effects, drug interactions, adherence and cost. A limited evidence base is emerging to support the effectiveness of APP in clinical practice. Our companion paper highlighted the extent of APP alongside commonly prescribed long-acting antipsychotic injections (LAIs). We aimed to examine the effects of APP on discontinuation rates and Clinical Global Impression (CGI) outcomes in patients commenced on risperidone long-acting injection (RLAI) and zuclopenthixol decanoate. Method: LAI-naïve patients commenced on RLAI ( n = 102) and zuclopenthixol decanoate( n = 105) were identified using our electronic patient record (running from 2002) within NHS Lanarkshire, Scotland, UK. This was a retrospective, electronic case note review with an 18-month follow up. Patient groups were divided into those receiving the LAI as the sole antipsychotic and those who were receiving additional oral antipsychotic polypharmacy (APP) for at least 50% of the duration of the treatment with their LAI. Kaplan–Meier statistics were calculated for discontinuation rates. CGI severity and improvement scores were retrospectively assigned by the investigating team. Results: Antipsychotic polypharmacy occurred with RLAI (37%) and zuclopenthixol decanoate (46%) and was associated with lower discontinuation rates (statistical significant with zuclopenthixol for any cause and adverse effects discontinuation). APP had no adverse outcomes on hospital admissions or CGI ratings. Patients on APP did not have more severe, chronic or treatment resistant illnesses. Conclusions: For RLAI and zuclopenthixol decanoate, APP had some favourable outcomes when examining discontinuation rates for any cause, and adverse effects. This was unexpected as we had considered APP would signal illness chronicity and severity and be associated with increased adverse effects resulting in early discontinuation. APP had no adverse outcomes on assigned CGI improvement or mean end-point severity ratings for RLAI and zuclopenthixol decanoate.